Optimasi Minyak Atsiri Daun Nilam (Pogostemon cablin Benth) dan Minyak Atsiri Daun Sereh Wangi (Cymbopogon nardus L) sebagai Antibakteri Staphylococcus aureus pada Masker Gel Peel-Off - Vinca Yustisia Maharani; Anifatus Sa’adah; Silvy Aldila (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Acne is a disease that is of particular concern among teenagers and adults. Acne appears due to excessive activity of the oil glands and is made worse by infection with the Staphylococcus aureus bacteria. This problem can be overcome by using a combination of essential oils in a peel off gel mask which can inhibit Staphylococcus aureus bacteria. Purpose: : to analyze the optimum combination of essential oils, information on their physical characteristics and their ability to inhibit Staphylococcus aureus. Method: Simplex Lattice Design in Design Expert version 13.0, disk diffusion method, and Follin Ciaocelteau's Reagent (RFC) method. Results: The essential oils of patchouli and citronella leaves contain alkaloid, flavonoid, terpenoid and phenolic compounds, as well as patchouli alcohol, citronellal, genariol and citronellal which hav have the ability to inhibit Staphylococcus aureus bacteria with a very strong classification of 31.88 ± 2.74 mm, the total phenolic content values were 21.35 ± 0.15 mgGAE/g and 20.86 ± 0.04 mgGAE/g. In the SLD, the optimum combination is found to be 9.932%:10.068% with a desirability value of 0.976. Conclusion: The optimum formula is 9.932%:10.068% with a desirability value of 0.976. The optimum combination of patchouli essential oil and citronella has an influence on inhibitory power, spreadability, viscosity, pH, and dry time.